Unveiling the biogas potential of raw Agave leaf juice: Exploring a novel biomass source - de Paula, Maiki S.; Adarme, Oscar F. Herrera; Volpi, Maria Paula C.; Flores-Rodriguez, Carla I. [UNESP]; Carazzolle, Marcelo F.; Mockaitis, Gustavo; Pereira, Gonçalo A.G. (Elsevier, 2025)
The use of plants from the Agave genus as biomass for biofuel presents great potential for energy transition due to its physiological traits and non-competitiveness with food crops. Brazil, the largest producer of sisal, presents a promising opportunity to use agave residues as substrate for anaerobic digestion. However, few studies address the potential for conversion of raw juice extracted from these plants into methane. This study evaluated the physicochemical and composition characteristics of raw agave juice, as well as its impacts on anaerobic digestion for biogas production and energy recovery. Biochemical Methane Potential assays were conducted with agave juice at concentrations of 0.5, 2.5, and 5 gVS/L, both with and without nutritional supplementation. The substrate concentration and nutritional supplementation increased methane production by 3.77- and 2-fold, respectively, showing that increasing substrate concentrations — at constant substrate/inoculum ratio — and nutritional supplementation significantly boosts methane production from agave. This optimization yielded methane yields of up to 626.97 ± 33.20 NmL CH4/gVS, along with 49.81 kWh of electric energy and 332.98 MJ of thermal energy for each ton of processed agave leaves. These findings enhance our understanding of optimizing biogas production from agave juice, supporting the transition to sustainable energy.
Keywords: Agave; Anaerobic digestion; Biogas; Methane; Nutritional supplementation